2020
DOI: 10.3390/cancers12123661
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-Derived Fragments (tRFs) in Bladder Cancer: Increased 5′-tRF-LysCTT Results in Disease Early Progression and Patients’ Poor Treatment Outcome

Abstract: The heterogeneity of bladder cancer (BlCa) prognosis and treatment outcome requires the elucidation of tumors’ molecular background towards personalized patients’ management. tRNA-derived fragments (tRFs), although originally considered as degradation debris, represent a novel class of powerful regulatory non-coding RNAs. In silico analysis of the TCGA-BLCA project highlighted 5′-tRF-LysCTT to be significantly deregulated in bladder tumors, and 5′-tRF-LysCTT levels were further quantified in our screening coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Unsurprisingly, numerous research groups have identified tRFs as potential prognostic molecular markers in various cancer types [ 42 , 43 ]. Particularly, a high ratio of 5′-tRF-LysCTT/3′-tRF-PheGAA has been correlated with a worse prognosis in prostate cancer [ 44 ], while increased 5′-tRF-LysCTT levels were strongly linked to a poor disease outcome in bladder cancer [ 45 ]. Additionally, the reduced serum levels of 5′-half-ValCAC were associated with adverse clinicopathological characteristics [ 46 ], whereas the elevation of two i-tRFs derived from tRNA CysGCA was correlated to trastuzumab resistance and worse prognosis of breast cancer patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, numerous research groups have identified tRFs as potential prognostic molecular markers in various cancer types [ 42 , 43 ]. Particularly, a high ratio of 5′-tRF-LysCTT/3′-tRF-PheGAA has been correlated with a worse prognosis in prostate cancer [ 44 ], while increased 5′-tRF-LysCTT levels were strongly linked to a poor disease outcome in bladder cancer [ 45 ]. Additionally, the reduced serum levels of 5′-half-ValCAC were associated with adverse clinicopathological characteristics [ 46 ], whereas the elevation of two i-tRFs derived from tRNA CysGCA was correlated to trastuzumab resistance and worse prognosis of breast cancer patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are literally hundreds of studies purporting that dysregulation of tRFs is related to cancers of various types [ 108 , 109 , 110 ]; however, the underlying mechanisms remain largely unknown, both in terms of what alters tRNA processing and what signaling cascades are triggered by tRF dysregulation [ 20 ]. In addition to their potential utility as biomarkers, tRF levels might also indicate how well cells will respond to various kinds of therapy, though again mechanistic explanations remain poorly understood [ 103 , 111 ].…”
Section: Diversification Of Ncrna Functionmentioning
confidence: 99%
“…Likewise, Papadimitriou et al. reported a significant elevation of the tRF-Lys-CTT in bladder tumors and a positive association with clinical prognosis ( 115 ). Interestingly, data demonstrated diverse expression of three different tRF-5s in the testicular germinoma ( 120 ).…”
Section: Biological Processes Correlated With Tsrnasmentioning
confidence: 99%